GROWING THE NATIONALISM ATTITUDE OF STUDENT Case Study at Islamic Boarding School Al-Hadi Bojonegoro - Ni'mah, siti Mashurotu Khoirotun (http://jagadalimussirry.com/, 2020)
The attitude of nationalism among the student has still led to various opinions. This opinion raises various problems among students, namely not following the ceremony, not memorizing the great Indonesian songs, not memorizing the Pancasila, not raising the flag, not honoring each other. The formulas raised in this study are; (1) What is the meaning of nationalism; (2) How are the values ​​of nationalism in the perspective of the Qur'an; (3) How is the relationship between nationalism and the principle of unity in Pancasila; (4) How is the implementation of the values ​​of Pancasila to foster nationalism in the daily lives of students in the Al-Hadi Bojonegoro boarding school. (1) want to describe the understanding of nationalism; (2) want to describe the values ​​of nationalism in the perspective of nationalism; (3) want to describe the relation between nationalism and the value of the principle of unity in Pancasila; (4) wants to describe the implementation of Pancasila values ​​to foster nationalism in the daily lives of students in the Islamic boarding school Al-Hadi Bojonegoro. Data collection techniques in this study used interviews with informants.. There are five things that encourage the application of the attitude of Nationalism; (1) Awareness to be willing to sacrifice; (2) Proud becomes an Indonesian citizen; (3) Appreciate the services of the heroes; (4) Mutual respect for differences in religion; (5) Pride in Indonesian culture. From these five things as a whole the attitude of Nationalism has grown and developed in the personality of the students. Although in the era of globalization and technology which increasingly eroded the nationalist attitude which tends to prioritize their own interests and momentary gains in the students still have attitudes that encourage the growth of nationalism in themselves.